Hubungan Personal Hygiene dengan Kejadian Penyakit Scabies pada Santri di Pondok Pesantren Ar-Rofi’I Jagakarsa Jakarta Selatan - Khasanah, Rifka Amalia Uswatun; Putri, Rima Berlian; Iksan, Ricky Riyanto (VISA: Journal of Vision and Ideas, 2025)
Scabies is a skin disease that is often found in Indonesia. Scabies is caused by mites, namely Sarcoptes scabiei hominis varieties. Mites that enter the layers of the skin will form lesions that result in scabies infection. This study aims to determine the relationship between Personal Hygine and the incidence of scabies in students at the Ar-Rofi'i Jagakarsa Islamic boarding school, South Jakarta in 2023. This research design uses a quantitative design with a cross sectional design using the Correlation Study method. The total sample was 92 students using total population sampling. The instrument used is a questionnaire sheet. The results of the study showed that there was no relationship between personal hygiene and scabies in adolescents (1,000 > 0.05). In the chi-square statistical test, a p-value of 1,000 was obtained, which means the p-value was greater than the significant value α (1,000 > 0.05). So it can be concluded that there is no significant relationship between personal hygiene behavior and scabies in students at the Ar-Rofi'I Jagakarsa Islamic boarding school, South Jakarta. Based on the results of the research, it is hoped that this researcher can add insight and information and can become a source of information to find the main factors of personal hygiene which are one of the triggers for the occurrence of scabies.